THE THEORY OF PLANNED BEHAVIOR AND PERCEIVED STRESS REDUCTION IN THE PREVENTION OF CARDIOVASCULAR DISORDER - Carpi Ballester, Amparo; Breva Asensio, Alicia; Palmero Cantero, Francisco (Anales de Psicología / Annals of Psychology, 2005)
This study analyses the importance of intention as a motivating variable in the reduction of perceived stress in the prevention of disease, and in particular, of any type of cardiovascular disorder. We have used the Theory of Planned Action (TPA) model to discover and comprehend the variables that have a positive effect on the intention to follow a certain behaviour pattern. The sample studied is made up of 360 members of the general public who at present, do not display any cardiovascular disorder. With the statistical program SPSS (12.00) we analized the general descriptive characteristics of the sample. In order to prove the adjusting grade of the model and in order to know the influence of the different variables in the prediction of the behavior intention, we have used the statistical program of equations of structural models EQS (Bentler, 2004).